The Cambridge companion to Heidegger - Guignon, Charles B (Cambridge University, 2013)
Martin Heidegger is now widely recognised alongside Wittgenstein as one of the greatest philosophers of the twentieth century. He redefined the central task of philosophy as the investigation of the nature of being, and has exerted a profound impact on literary theory, theology, psychotherapy, political theory, aesthetics, environmental studies, as well as mainstream philosophy. His thought has contributed to the recent turn to hermeneutics in philosophy and the social sciences, and to current post-modern and post-structuralist developments. The disclosing of his deep involvement in the ideology of Nazism has provoked much debate about the relation of philosophy to politics. This volume contains both overviews of Heidegger's life and works and analysis of his most important work, Being and Time. In addition there are discussions of Heidegger's thought in relation to mysticism, traditional theology, ecology, psychotherapy and the philosophy of language. The volume also contains the first in-depth study of what has been called Heidegger's second greatest work, the Beitrage zur Philosophie.